2006
DOI: 10.1039/b604843a
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the bonding in Mn(η2-SiH) complexes by charge density analysis and T1NMR measurements: asymmetric oxidative addition and anomeric effects at silicon

Abstract: The bonding in Mn(eta2-SiH) complexes is interpreted in terms of an asymmetric oxidative addition whose extent is controlled by the substitution pattern at the hypercoordinate silicon centre, and especially by the ligand trans to the eta2-coordinating SiH moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
60
0
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 22 publications
9
60
0
8
Order By: Relevance
“…the η 2 -SiH bond shortening, must be considered as normal. Therefore, there is no need to invoke the hypervalent properties of Si 12,15 when trying to explain the η 2 -SiH bond shortening if halogen is present at position either 1 or 2 in the -SiR 3 group of Cp(OC) 2 Mn[η 2 -H(SiR 3 )]. Instead, it is simply a result of the inductive influence of halogen atoms as clearly shown in this article.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…the η 2 -SiH bond shortening, must be considered as normal. Therefore, there is no need to invoke the hypervalent properties of Si 12,15 when trying to explain the η 2 -SiH bond shortening if halogen is present at position either 1 or 2 in the -SiR 3 group of Cp(OC) 2 Mn[η 2 -H(SiR 3 )]. Instead, it is simply a result of the inductive influence of halogen atoms as clearly shown in this article.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, from this point of view, the trans position at -SiR 3 is unique in Cp(OC) 2 Mn[η 2 -H(SiH 3−n X n )] and similar complexes. 2 We have very recently shown 18 that, contrary to the well-known elongation of the η 2 -SiH bond caused by the presence of a halogen atom being trans to this bond, [15][16][17][18] halogens at other positions lead, instead, to the shortening of this bond. Thus, we have shown that the length of the η 2 -SiH bond in Cp(OC) 2 Mn[η 2 -H(SiH 3−n X n )] results from two opposite effects, i.e.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Associated with this is the desire to get more insight into the mechanism of Si-H bond activation by transition metal compounds [20][21][22][23][24][25][26][27][28][29] which in turn is relevant even for the topic of C-H bond activation [30] as well as for the understanding of transition metal-catalyzed oligo-and polysilane formation [31].…”
Section: Introductionmentioning
confidence: 99%